(untitled) (Journal of the College of Basic Education, 2023)
The two researchers pointed out that the rapid invasion of technology over the years on the lives of individuals, along with the pressures of life, has led many to neglect their health. What led to a noticeable rise and weight gain over the years is that attention to health includes not neglecting exercise. As for the importance of the message, it comes as an attempt to find out the effect of Pilates exercises accompanying nutritional awareness on some body measurements for women aged (25-35) years. The two researchers noticed the phenomenon of weight gain, especially among women, that is widespread, because they live a sedentary and sedentary life, rarely engage in sports activities, and not adhere to a healthy diet to maintain body weight as a result of poor nutritional awareness, so the researchers decided to study this problem. Its aim is to identify the effect of Pilates exercises accompanying nutritional awareness on some functional indicators for women aged (25-35) years. The two researchers used the experimental method, which depends on collecting information and data related to the research topic. The two researchers identified the research community by the intentional method, and they are women aged (25-35) years who participate in fitness centers in Baghdad, and a random sample of (12) women practicing sports in the private halls of fitness centers in Baghdad was selected and the sample was chosen by random method. Functional indicators. The two researchers prepared special exercises for Pilates exercises, and gave lectures on nutritional awareness with three training units per week, and included presentation, analysis and discussion of the research results. It also included the conclusions and recommendations, that the adoption of Pilates exercises accompanying nutritional awareness reduces some functional indicators for women aged (25-35) years.